2022
DOI: 10.1101/2022.07.01.498398
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Loss of growth differentiation factor 9 causes an arrest of early folliculogenesis in zebrafish – a novel insight into its action mechanism

Abstract: Growth differentiation factor 9 (GDF9) is the best characterized growth factor released by the oocyte; however, most information about GDF9 functions comes from studies in the mouse model. In this study, we created a mutant for Gdf9 gene (gdf9-/-) in zebrafish using TALEN approach. The loss of Gdf9 caused a complete arrest of follicle development at primary growth (PG) stage. These follicles eventually degenerated, and all mutant females gradually changed to males through sex reversal, which could be prevented… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(21 citation statements)
references
References 98 publications
2
19
0
Order By: Relevance
“…Our recent study showed that the loss of gdf9 in zebrafish resulted in a complete arrest of follicles at PG stage without accumulation of cortical alveoli. Interestingly, this phenotype could be rescued by simultaneous mutation of inhibin α subunit ( inha -/-) (Chen et al, 2022). This raised an interesting question about the relationship between Bmp15 and inhibin.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our recent study showed that the loss of gdf9 in zebrafish resulted in a complete arrest of follicles at PG stage without accumulation of cortical alveoli. Interestingly, this phenotype could be rescued by simultaneous mutation of inhibin α subunit ( inha -/-) (Chen et al, 2022). This raised an interesting question about the relationship between Bmp15 and inhibin.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the loss of bmp15 and gdf9 resulted in follicle blockade at different developmental stages. The mutation of gdf9 caused a complete arrest of follicle development at PG stage without formation of cortical alveoli (PG-PV transition) (Chen et al, 2022) whereas bmp15 deficiency arrested follicles at PV stage (PV-EV transition) without any signs of vitellogenesis characterized by yolk granule accumulation. To study potential interactions between bmp15 and gdf9 , we generated a double mutant ( bmp15-/-;gdf9-/- ) using a gdf9 mutant we recently reported (ZFIN line number: umo18) (Chen et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations